2016
DOI: 10.3390/toxins8010027
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Bee Venom Derived Phospholipase A2 on Oxaliplatin-Induced Neuropathic Pain in Mice

Abstract: Oxaliplatin, a chemotherapy drug used to treat colorectal cancer, induces specific sensory neurotoxicity signs that are aggravated by cold and mechanical stimuli. Here we examined the preventive effects of Bee Venom (BV) derived phospholipase A2 (bvPLA2) on oxaliplatin-induced neuropathic pain in mice and its immunological mechanism. The cold and mechanical allodynia signs were evaluated by acetone and von Frey hair test on the hind paw, respectively. The most significant allodynia signs were observed at three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Consistent with these data, type IIA PLA 2 has been localized by immunohistochemistry to the spinal trigeminal and facial motor nuclei and dorsal- and ventral-horns of the spinal cord [36], implying an important role of CNS sPLA 2 in nociceptive transmission. It has also been shown that the treatment of mice with bee venom PLA 2 might prevent oxaliplatin-induced neuropathic pain [37]. Given our data shows an interaction of PP PLA 2 with α9α10 nAChR, we suggest that the PLA 2 interaction with this receptor may be involved in the pain transmission pathway.…”
Section: Discussionsupporting
confidence: 58%
“…Consistent with these data, type IIA PLA 2 has been localized by immunohistochemistry to the spinal trigeminal and facial motor nuclei and dorsal- and ventral-horns of the spinal cord [36], implying an important role of CNS sPLA 2 in nociceptive transmission. It has also been shown that the treatment of mice with bee venom PLA 2 might prevent oxaliplatin-induced neuropathic pain [37]. Given our data shows an interaction of PP PLA 2 with α9α10 nAChR, we suggest that the PLA 2 interaction with this receptor may be involved in the pain transmission pathway.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have demonstrated that boosting the Treg subpopulation through the intrathecal adoptive transfer of Tregs or the administration of the Treg-enhancing bee venom-derived phospholipase A 2 reduces chemotherapy-induced neuropathic pain in rodents. 104,106 With respect to regulatory cytokines, oxaliplatin-induced mechanohypersensitivity is associated with reduced levels of the anti-inflammatory cytokines IL-10 and IL-4 in the spinal dorsal horn. 107 Conversely, intrathecal IL-10 gene therapy or the intrathecal administration of recombinant IL-10 has been shown to progressively reverse the allodynic state associated with paclitaxel treatment.…”
Section: Contribution Of Nitro-oxidative Stress To Cipnmentioning
confidence: 99%
“…In this regard, boosting the endogenous anti‐inflammatory state might serve as another route to pain resolution in patients with CIPN. Several studies have demonstrated that boosting the Treg subpopulation through the intrathecal adoptive transfer of Tregs or the administration of the Treg‐enhancing bee venom‐derived phospholipase A 2 reduces chemotherapy‐induced neuropathic pain in rodents . With respect to regulatory cytokines, oxaliplatin‐induced mechanohypersensitivity is associated with reduced levels of the anti‐inflammatory cytokines IL‐10 and IL‐4 in the spinal dorsal horn .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the whole venom, some phospholipases A 2 isolated from the venom have been studied as analgesics. Li et al (2015) [ 99 ] demonstrated the analgesic effect of a bee venom-derived phospholipase A 2 (bvPLA 2 ) in a model of neuropathic pain. In this study, neuropathic pain was induced in mice, by a single infusion of oxaliplatin, a compound that is widely used to treat metastatic colorectal cancer.…”
Section: Antinociception Induced By Other Animal Venoms Spla mentioning
confidence: 99%